2022
DOI: 10.1038/s41467-022-32030-8
|View full text |Cite
|
Sign up to set email alerts
|

A practical concept for catalytic carbonylations using carbon dioxide

Abstract: The rise of CO2 in atmosphere is considered as the major reason for global warming. Therefore, CO2 utilization has attracted more and more attention. Among those, using CO2 as C1-feedstock for the chemical industry provides a solution. Here we show a two-step cascade process to perform catalytic carbonylations of olefins, alkynes, and aryl halides utilizing CO2 and H2. For the first step, a novel heterogeneous copper 10Cu@SiO2-PHM catalyst exhibits high selectivity (≥98%) and decent conversion (27%) in generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 71 publications
0
23
0
1
Order By: Relevance
“…1, selected hydroformylations of lower aliphatic olefins and are shown utilizing cobalt 5 or rhodium complexes. 2,6 Notably, the drastic reaction temperatures and pressures in case of cobalt-catalysed carbonylations are required to ensure stability and formation of the active hydridocobalt carbonyl species. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, selected hydroformylations of lower aliphatic olefins and are shown utilizing cobalt 5 or rhodium complexes. 2,6 Notably, the drastic reaction temperatures and pressures in case of cobalt-catalysed carbonylations are required to ensure stability and formation of the active hydridocobalt carbonyl species. 7…”
Section: Introductionmentioning
confidence: 99%
“…1, selected hydroformylations of lower aliphatic olefins and are shown utilizing cobalt 5 or rhodium complexes. 2,6 Notably, the drastic reaction temperatures and pressures in case of cobaltcatalysed carbonylations are required to ensure stability and formation of the active hydridocobalt carbonyl species. 7 However, recently we 8 and others 9 reported that in the presence of suitable promoters or appropriate reaction conditions, cobalt-catalysed hydroformylation of olefins with syngas could proceed under relatively mild conditions with good aldehyde yields and regioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] In organic synthesis, so far, the major focus has been given towards the formation of novel C-C bonds, C-heteroatom bonds, and others by using this strategy. [18][19][20] It should be clearly noted that in all of the cases, pure CO2 gas has been used as the carbon source, and to the best of our knowledge, impure CO2 stream such as the direct use of the flue gas collected from industries or exhaust gas collected from a car has rarely been reported. However, if an impure CO2 stream can be used, it certainly avoids the associated cost and energy requirement for the CO2 purification procedure and provides a new direction for the application of the Carbon Capture and Utilization (CCU) principle.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, H 2 can be used for selective reduction of carbon dioxide (CO 2 ) to CO (reverse water gas shift reaction), which offers new perspectives in CO 2 sequestration and valorization. 9,10 For all these applications, there is a need for reliably monitoring of the concentrations of both H 2 and CO in chemical plants, in fuel cells, and in an ambient environment.…”
mentioning
confidence: 99%
“…However, traces of CO (in low ppm concentrations) may compromise the performance of proton-exchange membrane fuel cells (PEMFCs), acting as a poison to the anode. , The utilization of biomass for the production of hydrogen and other synthetic fuels as well as many other chemicals is also receiving increasing attention. , In the latter context, both CO and H 2 occur simultaneously, such as in the water gas shift reaction . Carbon monoxide is also used for carbonylation of organic compounds or for the Fischer–Tropsch synthesis, to name just a few examples. , In addition, H 2 can be used for selective reduction of carbon dioxide (CO 2 ) to CO (reverse water gas shift reaction), which offers new perspectives in CO 2 sequestration and valorization. , For all these applications, there is a need for reliably monitoring of the concentrations of both H 2 and CO in chemical plants, in fuel cells, and in an ambient environment.…”
mentioning
confidence: 99%